2020
DOI: 10.1007/s11695-020-04820-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Bariatric Surgery in African Americans: an Analysis of the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) Data Registry

Abstract: Background The incidence of obesity is disproportionally high in African Americans (AA) in the United States. This study compared outcomes for AA patients undergoing Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG) with non-AA patients. Methods The MBSAQIP database was reviewed for RYGB and SG patients (2015-2017). Patients were identified as AA or non-AA and grouped to RYGB or SG. Combined and univariate analyses were performed on unmatched/propensity matched populations to assess outcomes. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…In this study, non-White patients (including a majority of Black patients) compared to White patients were more likely to live within proximity of at least one LD food store within a 5-min walk. Similar to other published work [ 17 , 18 ], non-White patients had less weight loss over 24 months compared to White patients. Finally, non-White patients within a 5-min proximity of at least one LD selection store also had less weight loss at 24 months compared to their non-White peers within proximity of no LD selections stores.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, non-White patients (including a majority of Black patients) compared to White patients were more likely to live within proximity of at least one LD food store within a 5-min walk. Similar to other published work [ 17 , 18 ], non-White patients had less weight loss over 24 months compared to White patients. Finally, non-White patients within a 5-min proximity of at least one LD selection store also had less weight loss at 24 months compared to their non-White peers within proximity of no LD selections stores.…”
Section: Discussionsupporting
confidence: 89%
“…Minority populations in the United States bear a disproportionate burden of the obesity epidemic and its associated comorbidities and tend to undergo fewer bariatric procedures compared with non-Hispanic White populations, which may be associated with socioeconomic factors, limited access to health care, and/or insurance options. 55 , 56 In addition, recent studies have identified race as an important factor associated with weight fluctuations, remission of obesity-related comorbidities, lower weight loss, and higher rates of hospital resource utilization and mortality after bariatric surgery. 57 , 58 , 59 , 60 , 61 , 62 , 63 In our current study, reversal of microvascular and macrovascular dysfunction was evident in both White participants and participants who identified as a minority racial/ethnic group, but the factors associated with vascular remodeling differed between races.…”
Section: Discussionmentioning
confidence: 99%
“… 57 , 58 , 59 , 60 , 61 , 62 , 63 In our current study, reversal of microvascular and macrovascular dysfunction was evident in both White participants and participants who identified as a minority racial/ethnic group, but the factors associated with vascular remodeling differed between races. Minority populations have been associated with lower hypertension remission and higher mortality rates, 56 , 58 , 59 , 62 , 63 which may partly relate to abnormalities in vascular tone. Racial differences may exist in their anatomical and physiological properties, which warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the established efficacy of bariatric surgery for long-term weight loss and comorbidity resolution[ 1 – 5 ], there are health inequity trends [ 6 ] in which patients identifying as racial/ethnic minorities and from economically disadvantaged backgrounds have poorer postoperative outcomes [ 7 10 ]. Specifically, Black/African American patients experience increased major postoperative complications, 30-day readmissions, re-intervention, reoperation, mortality, less weight loss, and lower attendance rates compared to non-Black/African American patients [ 7 , 11 14 ]. Patients of low socioeconomic status (i.e., lower income, receiving governmental social assistance, etc.)…”
Section: Introductionmentioning
confidence: 99%